Los elementos geomorfológicos del cauce en el Ebro de meandros libres y su colonización vegetal - Ollero Ojeda, Alfredo (Geographicalia, 2017)
In the free meanders’streach of Ebro river (Logroño-La Zaida) the most significant geomorphological element of channel and floodplain (gravelbars, islands, channel closed, confluences, ox-bow lakes) are described and the installation of riparien vegetation (sotos) over there are analysed. Along the streach (at least 350 km) highlight form and processes’ homogeneity and its high geoecological dynamic. Channel closed and ox-bow lakes are principal geomorphological elements for development of most relevant and complex riparian ecosystem and now they are coming to an dessapear.